1, 2, 3-Triazole-gold(I)-triethylposphine derivatives active against resistant Gram-positive pathogens. (15th May 2021) - Michaut, Mathieu; Steffen, Alexandre; Contreras, Jean-Marie; Morice, Christophe; Schalk, Isabelle J.; Plésiat, Patrick; Mislin, Gaëtan L.A.
Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Abstract: Innovative organogold(I) antibacterial compounds were synthesized by click chemistry with triethylphosphine-gold(I) azides and an alkyne derivative. The resulting organo-gold(I) compounds exhibit high levels of antibacterial activity against Gram-positive pathogens, with particularly low MICs against Clostridium difficile .